1977
DOI: 10.1136/ard.36.4.374
|View full text |Cite
|
Sign up to set email alerts
|

Plasma uric acid and plasma albumin in healthy subjects.

Abstract: SUMMARY In healthy male subjects there was a positive correlation between plasma uric acid and plasma albumin (r=0O 43, P<0 .005, n=49) when repeated measurements of both variables were used for each subject. Changes in plasma albumin induced by in vivo ultrafiltration were not accompanied by changes in plasma uric acid. The correlation of plasma uric acid with plasma albumin cannot be attributed to protein binding of urate. The two variables are probably related indirectly through a common association with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…We identified 71 publications that contained information on albumin in nondiseased individuals (4)(5)(6)(7)(8)(9)(12)(13)(14)(15)(16)18,19,(21)(22)(23)(24)(25)(26)28,29,32,33,35,36,45,46,(54)(55)(56)(58)(59)(60)(62)(63)(64)(65)(66)(67)(68)(69)(70)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…We identified 71 publications that contained information on albumin in nondiseased individuals (4)(5)(6)(7)(8)(9)(12)(13)(14)(15)(16)18,19,(21)(22)(23)(24)(25)(26)28,29,32,33,35,36,45,46,(54)(55)(56)(58)(59)(60)(62)(63)(64)(65)(66)(67)(68)(69)(70)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…The positive significant correlation between Alb and UA in this study is in total agreement with that reported by Ramsay et al, who reported a positive correlation between plasma uric acid and plasma Alb (r=0.43, p<00.005, n=49) in healthy male subjects. 29 However, in COPD patients, there was considerable alteration in the correlation. Significant correlation between Alb and UA; Bil and UA; Alb and CAT; that was observed in the normal individuals was found lost in COPD patients while the correlation between SOD3 and CAT remained unaltered ( Table 2).…”
Section: Discussionmentioning
confidence: 99%